Performance evaluation of seed values and pause times over high speed Wireless Campus Network in IEEE802.11e - Alam Shishir, Md. Khorsed; Abd Latif, Suhaimi; Akter, Mahmuda; Hakak, Saqib Iqbal; Masud, Massarof H.; Anwar, Farhat (2014)
IEEE802.11e standard assures to provide QoS using service differentiation mechanism over WLAN. The Enhanced Distributed Channel Access (EDCA) mechanism employs to differentiate the multimedia traffic based on assigned priorities and allows accessing the channel.Only one category of traffic permits access to the channel at a time to avoid traffic collision over the network. In EDCA, the back-off window algorithm generates back-off window size randomly during traffic transmission through the channel to prevent other categories of traffic to access the channel. Due to this randomness of back-off window algorithm to provide probabilistic QoS to satisfy the multimedia traffic through the network, the random mobility model can reduce the network performance. In this paper, we analyze the proposed network performance based on the variation of randomness using different seed values according to different pause time and evaluate the network performance using various performance metrics in IEEE802.11e.